(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Rhesus alloimmunization is a significant cause of perinatal morbidity in sub-Saharan Africa. Case presentation: A 28-year-old para 2+2 gravida 5, rhesus-negative mother with no living child presented to the Kenyatta National Hospital (KNH) antenatal clinic at 20 weeks of gestation as a referral because of a bad obstetric history secondary to rhesus D alloimmunization following a positive indirect Coombs test. She was started on methylprednisolone, and serial middle cerebral artery peak systolic velocity (MCA-PSV) monitoring was performed until 32 weeks of gestation when the fetus developed hemolytic disease of the newborn diagnosed via cordocentesis. She underwent two sessions of intrauterine transfusion and had a successful cesarean delivery at 34 weeks and 1 day of gestation. The neonate was admitted to the KNH neonatal intensive care unit where he was managed for hemolytic disease of the newborn, 33 days after which he was successfully discharged home. Conclusion: The role of maternal-fetal specialists in the diagnosis, antenatal follow-up, and timely management of rhesus D alloimmunization is key in the prevention of adverse perinatal outcomes.